Development of a Web-Based Employee Attendance Information System Using Agile Method - Nur Apriliani, Hilda; Pamungkas, Bayu (Ma'soem University, 2026)
Employee attendance plays a crucial role in human resource management; however, at Perumda Tirta Intan Garut, the attendance process is still conducted manually, leading to recording errors, delays in data recapitulation, and difficulties in monitoring employee discipline. This study aims to develop a web-based employee attendance information system using the Agile Development method to improve the efficiency, accuracy, and effectiveness of attendance management. The research employs a Research and Development (R&D) approach combined with Agile Methodology, allowing iterative system development and continuous user feedback. System modeling is carried out using Unified Modeling Language (UML), including use case, activity, sequence, and class diagrams. The system is implemented using the Laravel framework and a MySQL database, while functional testing is conducted using Black Box Testing. The results indicate that the developed system enables real-time attendance recording, reduces data entry errors, accelerates attendance report generation, and improves user satisfaction. This study contributes practically by providing an adaptive and efficient web-based attendance system and methodologically by demonstrating the effectiveness of Agile Development in information system development within public service organizations.